Business strategy of home healthcare service to accelerate the adoption of care at home service in Indonesia - Muhammad Naufal Syafrun; Ang Dung Do; Raden Aswin Rahadi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
The demand for value, shifts in consumer behavior, patients need, and a highly competitive market are driving many health-care providers to seek new and more effective methods of improving care delivery. This study aims to identify critical adoption factors by the patient to adopt the services and create a strategic positioning for HOSPON to gain competitive advantage. This conceptual research framework is done using the Analysis, Formulation, and Implementation (AFI) framework of strategic management. This research method uses qualitative and quantitative methods, with data collection carried out online and offline using in-depth interviews and questionnaires. The data analysis was carried out by content analysis and Analytical Hierarchy (AHP) process to determine the critical adoption factor of home healthcare services by carried out 4 criteria and 16 criteria. The AHP is a methodical framework that establishes a hierarchical structure with interdependent layers, analyzes the weight of various aspects, and evaluates potential courses of action depending on the structure already in place. Home healthcare services are identified as having four main stakeholders, i.e., patients, providers, policy makers, and payers. Integrating these four stakeholders is the most important thing to determine what factors should be developed and implemented to increase the adoption factor. Economic viability and law, professional capabilities, patient needs, and breadth of services are some of the factors that influence patient adoption of awareness and trustworthiness in using home healthcare services. The business solution from the research crate strategy formulation, the Generic business strategy that is implemented is the differentiation strategy which is explained in the five major of element strategy diamond models in its application to focus on health preventive care, health maintenance care, and post- acute care to operate in the high geographic mobility area to target the premium market with the patient who are aware of their medical needs. This is done by providing technology to connect between patients and providers to gain more trust, integrating to facility-based care to provide more comprehensive health care, and leveraging methods of work effect of the ecosystem to ensure insurance as payment and patient protection and provide more value creation. From the results of this study, each stakeholder can use this research as a basis for making decisions to determine organizational steps to increase the adoption rate of care at home services, to dissect regulations, and to implement the most effective payment schemes for home healthcare services.